Estimating the economic benefits of alternative options for investing in agricultural climate services in Africa: A review of methodologies - Tesfaye, Abonesh; Hansen, James; Radeny, Maren A.O.; Solomon, Dawit (2018)
Smallholder farmers in Africa are especially vulnerable to climate fluctuations and weather extremes, and are expected to suffer disproportionately from climate change. Climate services empower the poor particularly in climate-sensitive developing countries such as the ones in Africa, and allow them to reduce exposure and vulnerability of their agricultural sector to climate-related extreme events. Hence, the importance of investing in the enhancement of generating and delivery system of climate services to the resource poor farming communities of the continent provides a low regret adaptation to future climate change. This report reviews the suitability of ex-ante evaluation methods for informing funding agencies, private sectors, and other national and regional stakeholders about the benefits of alternative investment options in climate services. The review considers relevant and recent studies taking into account the agricultural sector. The review shows that economic modelling and stated preference approaches have the widest use and potential to estimate the benefits of climate services in Africa. However, comparison of the advantages and disadvantages of the methods conveys a message that there is no one type of method that fits into all different cases in estimating the benefits of climate services. Therefore, depending on particular cases, it would be necessary to use the appropriate method or combination of methods to enhance agricultural productivity, food and nutrition security, and the resilience of the resource poor vulnerable smallholder farming communities to climate variabilities and change in Africa.